Correlations of CT Scan Findings in Different Types of Cerebral Palsy: A Study in a Tertiary Care Centre in Bangladesh (Bangladesh Journal of Child Health, 2022)
Introduction: Cerebral palsy (CP) is one of the most common causes of chronic childhood disability. CT scan is helpful for identification of structural abnormalities, etiology, categorize the types of brain lesions and planning of intervention in the child with CP.Objective: This study was done to find relationship between types of CP and CT scan findings of brain.Materials and methods: This cross sectional descriptive study was done among 110 clinically diagnosed CP case from department of Paediatric Neurology & IPNA, BSMMU, during March 2016 to August 2017. Demographic, clinical characteristics & physical examination were done & collected data were recorded. CT scan of brain was done in all cases & all data were analyzed.Results: The mean age of the studied children was 2.6±2.2 years (1 to 14 years). Among them quadriplegic CP were the most common (39.1%), followed by 28.2% cases of hemiplegic CP, 16.4% were of mixed type, 7.3% were diplegic. Most common finding on CT scan of brain was cerebral atrophy (62.7%), followed by encephalomalacia (15.5%), calcification (13.6%), and brain malformations (11.8%). Abnormal CT scan findings were found in 88.2% of studied children. Children with hemiplegic CP had brain atrophy in 87% of cases, calcification was found mostly in quadriplegic CP. Brain malformation was found mostly in mixed type of CP.Conclusion: Most common CT scan finding was brain atrophy and commonly found in hemiplegic CP. Encephalomalacia and calcifications were commonly found in quadriplegic CP. Brain malformation were commonly found in mixed type of CP.BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 67-73